Riding the Waves of Technology: A Study into How SMEs Select Computerized Accounting Software (CAS) supplier in Developing Countries - Aduamoah, Maurice (Archives of Business Research, 2017)
Many SMEs are foreseeing the immense benefits of implementing CAS to facilitate the processing of their financial reporting. This Phenomenon has led to the spread of many CAS products in the software market, making it difficult to select the best among them for implementation. The sub-optimality of CAS is as a result of functionalities such as Scalability ;Capacity; Ease of Data Input ; Security; Speed of Installation ; CAS Consultant/Vendor ; Reporting Capabilities ; Error Handling ; Audit Trail ;Data Validation which are neglected as part of the selection process. CAS is either classified as off-the-shelf package (customised) or bespoke (custom designed).However, this paper concentrates on how SMEs managers select their off-the-shelf CAS (customised) packages in the mist of proliferations of many accounting software in the market. It examined the depth of information which served as guides to SME managers/owners in selecting their currently implemented CAS system. The methodology adopted for the study was the development of a structured questionnaire related to the functionality criteria’s above mailed to sample SMEs in the Kumasi Metropolis of Ghana to understand how SMEs choose their CAS packages. The results showed that SMEs desire CAS that are easy to use and vendor supplier.